2020
DOI: 10.1038/s41598-020-58730-z
|View full text |Cite
|
Sign up to set email alerts
|

Study of Structural stability and formation mechanisms in DSPC and DPSM liposomes: A coarse-grained molecular dynamics simulation

Abstract: Liposomes or biological vesicles can be created from cholesterol, phospholipid, and water. Their stability is affected by their phospholipid composition which can influence disease treatment and drug delivery efficacy. In this study, the effect of phospholipid type on the formation and stability of liposomes using coarse-grained molecular dynamics simulations is investigated. For this purpose, the simulation study of the DSPC (1,2-distearoyl-sn-glycero-3-phosphocholine) and DPSM (Egg sphingomyelin) lipids were… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
44
0
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 67 publications
(45 citation statements)
references
References 61 publications
0
44
0
1
Order By: Relevance
“…A key concern associated with employing nanomaterials as additives to advance material properties is the quality of the nanomaterial including composition, size, agglomeration status, high surface area, and noble physico-chemical properties [3,[12][13][14]34]. To address these concerns the employed gold nanowires, superparamagnetic iron oxide nanoparticles (SPION), graphene sheets, and graphene quantum dots were synthesized in-house and characterized using transmission electron microscope (TEM), Fourier-transform infrared spectroscopy (FTIR), scanning electron microscope (SEM), X-ray diffraction (XRD), and ultraviolet-visible spectroscopy (UV).…”
Section: Nanomaterials Synthesis and Characterization Of Nanostructurementioning
confidence: 99%
See 2 more Smart Citations
“…A key concern associated with employing nanomaterials as additives to advance material properties is the quality of the nanomaterial including composition, size, agglomeration status, high surface area, and noble physico-chemical properties [3,[12][13][14]34]. To address these concerns the employed gold nanowires, superparamagnetic iron oxide nanoparticles (SPION), graphene sheets, and graphene quantum dots were synthesized in-house and characterized using transmission electron microscope (TEM), Fourier-transform infrared spectroscopy (FTIR), scanning electron microscope (SEM), X-ray diffraction (XRD), and ultraviolet-visible spectroscopy (UV).…”
Section: Nanomaterials Synthesis and Characterization Of Nanostructurementioning
confidence: 99%
“…Recently, nano-engineered materials have been widely applied in the areas of drug delivery, biosensing, stem cells, biomedical science, nanotoxicity evaluation, and tissue engineering [3,[10][11][12][13][14][15][16]. For instance, osteoblast and stem cells cultured on nano-scaffold have long slender morphology on adhesion to neighbor cells; however, the cells cultured in solid scaffold have flat and smooth morphology [17][18][19][20].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…In liposome research fields, phospholipids with a higher phase transition temperature (T c ) than 37 • C have been regarded as more stable and sustained release carriers compared to those with lower T c [58][59][60]. As shown in Table 1, several liposomes included high T c phospholipids such as DMPC (24 • C, DPPC (41 • C), DSPC (55 • C) and HSPC (52 • C).…”
Section: Modulation Of Lipid Compositionsmentioning
confidence: 99%
“…Concerning liposomes, Hashemzadeh et al [169] recently reported the use of coarse-grain MD simulation to investigate the behavior of liposomes formed by 1,2-distearoyl-sn-glycero-3-phosphocholine (DSPC) and DPSM (Egg sphingomyelin). The results of the simulations indicated that even if DSPC and DPSM are usually used to generate liposomes and micelles, during the simulations of the self-assembly process, they form some nanodisc structures.…”
Section: Computational Chemistry In the Design Of Ddsmentioning
confidence: 99%